Participação do CD40L solúvel e da metaloproteinase de matriz -9 na resposta imune na leishmaniose visceral humana - Oliveira, Fabrícia Alvisi de (2016)
In the present study, the sera levels of soluble CD40 ligand (sCD40L) and matrix metalloproteinase-9 (MMP-9) were quantified by Luminex assay in Visceral leishmaniasis patients before and during treatment follow-up and after regular antimony treatment and also in individuals exposed to infection, living in endemic areas. Different from the other molecules present in sera from classic VL patients, sCD40L and MMP-9 are fairly increased, and increase over time during the follow-up of VL patients undergoing antimony treatment. sCD40L and MMP-9 sera levels were also high in individuals living in endemic settings at high risk of infection (endemic controls). On the other hand, sCD40L and MMP-9 were not observed in sera from non-endemic controls, which are not exposed of infection. Additionally, negative correlations were found between spleen sizes and MMP-9 before treatment and sCD40L at day 15 of treatment. Negative correlations were also found between parasite load with both sCD40L and MMP-9. These findings indicate that both molecules can be used in monitoring therapeutic efficacy in VL. Furthermore, these data suggest a protective effect of these molecules, since the individuals exposed to infection without the symptoms of disease have high sera levels of sCD40L and MMP-9. These data were published in BMC Infectious diseases journal [1]. To confirm the protective effect of sCD40L present in sera of VL patients and determine if this molecule had biological activity, the ability of sera from patients containing high levels of this molecule sCD40L to control infection in vitro in Leishmania infantum infected macrophages, and the ability to induce cytokines production. Thereby, macrophages from of healthy donor were infected with Leishmnia infantum, and later incubated in presence of sera from individuals exposed to infection in presence of anti-CD40L. The infection was evaluated by counting of the number of infected macrophages/100 and the number of intracellular amastigotes/100 macrophages. The data showed that serum sCD40L decrease the number of infected macrophages and the number of intracellular amastigotes. The blockage of sCD40L activity with specific antibody, increase the infection. Moreover, the analysis of cytokines in supernatant of these macrophage cultures by Luminex assay demonstrated that sCD40L induces the IL-12, IL-23, IL-27, IL-15 e IL-1 production. The levels of these cytokines is inversely correlated with infection rate and the number of intracellular parasites from infected macrophages. A second manuscript with these data were published in PLOS One [2] . These results demonstrated that serum sCD40L from individuals exposed to VL improve the microbicide effect and the inflammatory cytokine production, suggesting its potential use in VL immunotherapy. Nevertheless, there is still a long way to be approached in future experimental and clinical studies.